Tingkat Bauran Pemasaran Expedisi JNE Dalam Meningkatkan Keunggulan Bersaing Melalui Loyaitas Konsumen di Kecamatan Panai Hulu - Suci Yulianingsih; Ade Parlaungan Nasution; Fauziah Hanum (Journal of Trends Economics and Accounting Research, 2023)
This study aims to determine the effect of marketing mix mediated by consumer loyalty on competitive advantage, both direct and indirect influences. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. This study used a sample of 100 respondents, these respondents were individuals who had used services from JNE Panai Hulu District at least 2 times use, were over or equal to 17 years old, and were decision makers. By using non-probability sampling techniques. The hypothesis test is performed with the T test and the Sobel test. Data analysis using Partial Least Square (PLS) and assisted by SmartPLS 3.0 software to facilitate research From the results of this test, it can be concluded that the marketing mix variable has a positive and significant effect on the competitive advantage of JNE Panai Hulu District.